Plant AtEH/Pan1 proteins drive autophagosome formation at ER-PM contact sites with actin and endocytic machinery - Wang, Pengwei; Pleskot, Roman; Zang, Jingze; Winkler, Joanna; Wang, Jie; Yperman, Klaas; Zhang, Tong; Wang, Kun; Gong, Jinli; Guan, Yajie; Richardson, Christine; Duckney, Patrick; et al. (Nature communications, 2019)
The Arabidopsis EH proteins (AtEH1/Pan1 and AtEH2/Pan1) are components of the endocytic TPLATE complex (TPC) which is essential for endocytosis. Both proteins are homologues of the yeast ARP2/3 complex activator, Pan1p. Here, we show that these proteins are also involved in actin cytoskeleton regulated autophagy. Both AtEH/Pan1 proteins localise to the plasma membrane and autophagosomes. Upon induction of autophagy, AtEH/Pan1 proteins recruit TPC and AP-2 subunits, clathrin, actin and ARP2/3 proteins to autophagosomes. Increased expression of AtEH/Pan1 proteins boosts autophagosome formation, suggesting independent and redundant pathways for actin-mediated autophagy in plants. Moreover, AtEHs/Pan1-regulated autophagosomes associate with ER-PM contact sites (EPCS) where AtEH1/Pan1 interacts with VAP27-1. Knock-down expression of either AtEH1/Pan1 or VAP27-1 makes plants more susceptible to nutrient depleted conditions, indicating that the autophagy pathway is perturbed. In conclusion, we identify the existence of an autophagy-dependent pathway in plants to degrade endocytic components, starting at the EPCS through the interaction among AtEH/Pan1, actin cytoskeleton and the EPCS resident protein VAP27-1.
Keywords: buněčná membrána; Actin-Related Protein 2-3 Complex; proteiny huseníčku; Actin Cytoskeleton; Phylogeny; Protein Binding; aktiny; Saccharomyces cerevisiae - proteiny; Models, Biological; mikrofilamentové proteiny; Arabidopsis Proteins; Endocytosis; autofagie; Autophagosomes; endocytóza; komplex proteinů 2-3 souvisejících s aktinem; Saccharomyces cerevisiae Proteins; Arabidopsis; autofagozomy; Endoplasmic Reticulum; fylogeneze; vazba proteinů; biologické modely; Microfilament Proteins; Actins; endoplazmatické retikulum; Cell Membrane; Autophagy; mikrofilamenta